Morphometric analysis of small watershed using Geographical Information System and Remote Sensing - KUMAR, LOVE; KHALKHO, DHIRAJ; PANDEY, V. K.; SINHA, MANISH KUMAR; SINGH, PRASHANT; NIGAM, GAURAV KANT (Journal of Soil and Water Conservation, 2020)
Remote sensing and GIS techniques are being extensively used since quite some time in watershed related studies as very effective tools in determination of the basin geometry i.e, morphometric analysis or quantitative description of watershed morphologic characteristics. In the present study, an attempt has been made to use the capabilities of GIS (ArcGIS 10.4) to quantify the morphology of the Maniari watershed. The watershed was studied for its size and shape, drainage and relief characteristics to develop a thorough understanding of the watershed for future planning to avert the land degradation. Twenty three morphometric parameters of the Maniari watersheds situated in Lormi block of Mungeli District (Chhattisgarh), have been quantified. They comprise: Stream Order, Stream Length (Lu), Mean stream length (Lsm), Stream Length ratio (RL), Bifurcation ratio (Rb), Mean bifurcation ratio (Rbm), Drainage Density (Dd), Length of overland flow (Lg), Basin length (Lb), Basin perimeter (P), Basin/drainage area (A), Compactness constant (Cc), Stream frequency (Fs), Circulatory ratio (Rc), Elongation ratio (Re), Form Factor (Rf), Watershed shape factor (Ws), Drainage Texture (Rt), Total relief (H), Relief ratio (Rh), Relative relief (Rp) and Ruggedness number (Rn). On the basis of the morphometric studies it was concluded that the hydrologic response of the Maniari watershed is dependent on surface characteristics significantly due to its being a â€œFan Shapedâ€ one. The watershed is in active stage of degradation. Its quantification is being done based on the field measurements and recording of soil erosion. The result suggests that the ratio between cumulative stream length and stream order is constant throughout the successive orders of the basin.